A comprehensive analysis and hardware implementation of control strategies for high output voltage DC-DC boost power converter - Padmanaban, Sanjeevikumar; Grandi, Gabriele; Blaabjerg, Frede; Wheeler, Patrick; Siano, Pierluigi; Hammami, Manel (Atlantis Press, 2017)
Classical DC-DC converters used in high voltage direct current (HVDC) power transmission systems, lack in terms of efficiency, reduced transfer gain and increased cost with sensor (voltage/current) numbers. Besides, the internal self-parasitic behavior of the power components reduces the output voltage and efficiency of classical HV converters. This paper deals with extra high-voltage (EHV) dc-dc boost converter by the application of voltage-lift technique to overcome the aforementioned deficiencies. The control strategy is based on classical proportional-integral (P-I) and fuzzy logic closed-loop controller to get high and stable output voltage. Complete hardware prototype of EHV is implemented and experimental tasks are carried out with digital signal processor (DSP) TMS320F2812. The control algorithms P-I, fuzzy logic and the pulse-width modulation (PWM) signals for N-channel MOSFET device are performed by the DSP. The experimental results provided show good conformity with developed hypothetical predictions. Additionally, the presented study confirms that the fuzzy logic controller provides better performance than classical P-I controller under different perturbation conditions.